أثر مخاطر نظم المعلومات المحاسبي على جودة المعلومات المحاسبية - زين, عبد المالك; دراوسي, مسعود (University of Eloued جامعة الوادي, 2019)
تهدف هذه الدراسة إلى التعرف على المخاطر التي تواجه نظام المعلومات المحاسبي في البيئة الجزائرية، والتعرف على أهم الأسباب التي تؤدي إلى حدوث تلك المخاطر وأثرها على المعلومة المحاسبية والإجراءات المتخذة للحد من تلك المخاطر، وذلك من خلال استبان موزع مستخدمي نظم المعلومات المحاسبية في المؤسسات ومكاتب المحاسبة في ولايات الوادي، ورقلة وبسكرة، وقد توصلت الدراسة الى بعض النتائج منها قد تتعرض نظم المعلومات المحاسبي الى مخاطر أثناء تشغيلها هذه المخاطر في الغالب تكون نتيجة لأسباب داخلية، ولهذه المخاطر اثر على جودة المعلومة المحاسبية التي تعتبر مخرجات هذا النظام، ولتفادي هذه المخاطر لغرض تحسين جودة المعلومة المحاسبية وجب اتخاذ إجراءات لحماية نظام المعلومات المحاسبي. Abstract: This study aims to identify the risks facing the accounting information system in the Algerian environment. So that we could get to know and to identify the main reasons that lead to these risks and their impact on the accounting information and the measures taken to reduce these risks. The study has reached the following results: the accounting information systems may be exposed to risks during its operation. These risks are mostly due to internal reasons. These risks affect the quality of the accounting information that is the outputs of this system. Efforts have been made to improve the quality of accounting information. Hence, to avoid potential risks measures must be taken to protect the accounting information system.
The impact of the accounting information system's risk on the quality of accounting information
مقال - مجلة رؤى اقتصادية
Keywords: نظم المعلومات؛ جودة المعلومة المحاسبية؛ المخاطر.; Accounting Information Systems; The Quality of Accounting Information; Risk. Jel Classification Codes : L15; D83; M41 ;D81.